Optimalisasi Ketertiban Masyarakat: Pemberdayaan UMKM Melalui Inisiatif Pelayanan Terdedikasi - Esthi Dippoprameswari; Wahyu Eko Pujianto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research aims to explore and explain efforts to optimize public policy by strengthening micro, small, and medium enterprises (MSMEs) through the implementation of special service initiatives. Research methods include field surveys, interviews, and data analysis to gain comprehensive insight into the impact of service initiatives on MSMEs and local communities. The research results show that significant improvements in public policy and strengthening MSMEs can be achieved through special service strategies. Active support from stakeholders such as local governments, financial institutions, and local communities is key to the success of this initiative. In addition, community participation in the development and implementation of special service programs creates opportunities for increased cooperation and active participation in joint efforts to achieve common goals. These results are an important contribution for stakeholders, especially local governments and related institutions, in developing more effective policies to support public policy and strengthen MSMEs. It is hoped that the results of this research will produce practical guidelines for implementing specific service initiatives that can be adopted by various stakeholders to achieve sustainable development at the local level.